2018
DOI: 10.1016/j.jcin.2017.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Angiographic, and Procedural Correlates of Very Late Absorb Scaffold Thrombosis

Abstract: In the present analysis, the largest to date of its type, relative scaffold undersizing was the strongest determinant of VLST. Given current understanding of "scaffold dismantling," this finding likely has ramifications for all bioresorbable scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Both meta‐analyses have looked at outcomes at early and mid‐term follow‐up period that is, before 3 years, which is the time taken for the PLLA polymer to resorb. This is an important factor, among others such as inappropriate patient selection, inherent limitations of first generation BVS with thick stent struts and limited expansion capability, poor implantation technique, shorter DAPT duration, and deployment of BVS in small vessels, which might have led to poorer outcomes compared to DES . Among these, the importance of proper implantation technique (adequate pre‐dilation with a non‐compliant balloon, BVS implantation only after confirmation of adequate pre‐dilations and post‐dilation with a non‐compliant balloon) was demonstrated by a study done by Puricel et al, which showed a decrease in DT from 3.3 to 1.1% at 12‐months follow‐up when proper implantation technique was used…”
Section: Discussionmentioning
confidence: 99%
“…Both meta‐analyses have looked at outcomes at early and mid‐term follow‐up period that is, before 3 years, which is the time taken for the PLLA polymer to resorb. This is an important factor, among others such as inappropriate patient selection, inherent limitations of first generation BVS with thick stent struts and limited expansion capability, poor implantation technique, shorter DAPT duration, and deployment of BVS in small vessels, which might have led to poorer outcomes compared to DES . Among these, the importance of proper implantation technique (adequate pre‐dilation with a non‐compliant balloon, BVS implantation only after confirmation of adequate pre‐dilations and post‐dilation with a non‐compliant balloon) was demonstrated by a study done by Puricel et al, which showed a decrease in DT from 3.3 to 1.1% at 12‐months follow‐up when proper implantation technique was used…”
Section: Discussionmentioning
confidence: 99%
“…Bioresorbable scaffolds were introduced based on the concept that a permanent implant may represent a continuous stimulus for inflammation, platelet activation, and neointima proliferation. In previous publications, the mechanisms and predictors of events up to ≈3 years after BRS implantation were described [5][6][7][8][9][10][11][12]. We extend this information with an analysis of the incidence and predictors of events up to 5 years in the present paper.…”
Section: Target Lesion Failure In Stent-studiesmentioning
confidence: 61%
“…For instance, studies [8,10] identified a small (<2.5 mm) reference vessel size as the principal mechanism of early (<30 day) ScT; in contrast, implantation in large (>3.5 mm) vessels was associated with late events, suggesting that malapposition and scaffold strut discontinuities during resorption might predispose to this event. We and others previously described how the mechanical/physical characteristics of first-generation scaffolds may explain these associations [6,7]. In these papers, consistent evidence was produced that the thicker struts of BRS might cause flow turbulence leading, particularly in settings of incompletely expanded scaffolds (early device thrombosis) or malapposition (late thrombosis), to both platelet aggregation and neointima proliferation and to an increased risk of events.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations